Skrining dan Penyuluhan untuk Pengendalian Tekanan Darah - Zita Atzmardina; Firdani Mutiara; Louis Valdo; Silvia Damayanti; Rachel Ratu (STIKes Ibnu Sina Ajibarang, 2024)
Hypertension is an increase in blood pressure above normal values ​​due to various factors. Normal hypertension values ​​are in the range of 90/60 mmHg to 120/80 mmHg. Systolic pressure values ​​of more than 139 mmHg and diastolic pressure of more than 89 mmHg are categorized as hypertension. With increasing prevalence, hypertension is becoming a global health problem. In the world, an estimated 1.13 billion people aged 30 to 70 years suffer from hypertension, and this disease is a major risk factor for cardiovascular disease and stroke. In Indonesia, the prevalence of hypertension is estimated to reach more than 40% in the adult population in 2019 (WHO, 2019). The purpose of this activity is to prevent an increase in the prevalence of hypertension. The method used is to provide counseling and screening for hypertension risk factors. The results obtained are blood pressure data, anthropometry and hypertension exercises. It can be concluded that this activity was successful because there was an increase in the pre-test to post-test value of 25.21 points so that this activity can be sustainable to prevent hypertension patients.